Corrosion Inhibition of carbon steel XC70 in two acidic media (0.1 N H2SO4 (and (0.1 N HCl) by weight loss method using Black Pepper Extract as corrosion inhibitor (Al-Mukhtar Journal of Basic Sciences, 2025)
Black pepper (Piper Nigrum L.) extract and ecologically friendly inhibitor were employed in this investigation. According to the data, the corrosion rate in the hydrochloric acid medium (HCI) is greater than the corrosion rate in the sulfuric acid (H2SO4) medium. The corrosion rate of carbon steel varies depending on the corrosion medium. With an increase in inhibitor concentration, the percentage of inhibition increases. By using electron impact mass spectrometry, the mass fragmentation routes of several piperines from black pepper (Piper Nigrum L.) were examined (EI-MS). Different intensities of the molecular ion peaks M+2 and M+ were captured. By successively losing simple functional groups, followed by the breakdown of the heterocycles attached to the pyrimidine ring, distinctive fragment ions were created.